Flux and dynamics of iron and aluminium in wetlands of Kuttanad and its management for rice (Oryza sativa L.) - Ebimol, N L (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2017)
The investigation entitled “Flux and dynamics of iron and aluminium in wetlands of Kuttanad and its management for rice (Oryza sativa L.)” was carried out at College of Agriculture, Padannakkad during 2015-2017. The objective of the study was to evaluate the performance of two popular rice varieties viz. Uma and Prathyasa to varying levels of iron and aluminium concentrations at different growth stages and to examine suitable amelioration strategies. The entire experiment was conducted in three parts, which included collection and analysis of soil sample from Kuttanad, solution culture with graded levels of Fe and Al and a pot culture experiment using the Kuttanad soil. As a preparatory to pot culture study, an incubation experiment was also conducted using the bulk soil collected from Kuttanad so that nutrient release pattern under submergence could be obtained. Soil samples at GPS coordinates (latitude: 9°:18ˈ:56ˈˈ.99, longitude: 76°:24ˈ:30ˈˈ.68) were collected from the ‘Kari’ lands of Kuttanad and brought to College of Agriculture, Padannakkad and analysed for various physical and chemical properties. It was observed that the soil has extremely low pH, very low available P and toxic levels of Fe and Al. This soil was used for incubation study and pot culture experiment. The incubation study was conducted with four treatments at two levels of submergence (5 cm and 10 cm) in factorial CRD. The treatments were designed based on the recommendations of KAU POP 2011 viz. lime @ 600 kg ha-1 (T1); phosphogypsum + 1⁄2 lime @ 300 kg ha-1 (T2); magnesium carbonate @ 50 kg ha-1 + 1⁄2 lime @ 300 kg ha-1 (T3) and control (T4). During the submergence period among the various parameters monitored, a steady increase was observed for pH, Ca and Mg of the soil. Application of phosphogypsum + 1⁄2 lime showed the highest increase in soil pH and available calcium content and was highly effective in lowering the toxic concentration of Fe and Al in the acid sulphate soils of Kuttanad. The solution culture experiment was carried out using Hoagland’s nutrient solution as nutrient medium in which four levels of Fe (200, 400, 800 and 1200 mg L- 1 ) and two levels of Al (50 and 100 mg L-1) were added in factorial combination and experiment was designed in CRD. The treatment with 1200 mg L-1 Fe and 100 mg L-1 Al suppressed the plant height, root length, root dry weight and recorded maximum concentration of Fe and Al in the root and displayed thick iron coating (iron plaque) around the root as observed in the root sections. The third part of the investigation, pot culture experiment was conducted with seven treatments as amendments and two varieties Uma and Prathyasa in factorial CRD. The leachate was collected and analysed by placing a perforated pipe at the centre of the pot. The treatments were designed based on the recommendations of KAU POP 2011. The treatment combinations were: lime @ 600 kg ha-1 (T1); magnesium carbonate @ 50 kg ha-1 + 1⁄2 lime @ 300 kg ha-1 (T2); phosphogypsum + 1⁄2 lime @ 300 kg ha-1 (T3); lime @ 600 kg ha-1 + potassium silicate 0.25% + 0.25% boron (T4); magnesium carbonate @ 50 kg ha-1 + 1⁄2 lime @ 300 kg ha-1 + potassium silicate 0.25% + 0.25% Boron (T5); phosphogypsum + 1⁄2 lime @ 300 kg ha-1 + potassium silicate 0.25% + 0.25% boron (T6) and control (T7). The application of amendments significantly improved the biometric characters. The treatment T4 showed higher plant height and grain yield per pot whereas T6 showed more number of tillers and maximum number of grains per panicle. The treatment T6 considerably reduced the Fe, Al and Mn content in soil and leachate, which also recorded significantly higher of P, Ca, B and Si content in soil and leachate. The treatment T6 also recorded highest plant nutrient concentrations of N, P, K, Ca, S and B while significantly reduced the concentration of Fe and Al whereas the treatment T4 reduced the Mn content, increased the Si content and maximum increase in value of soil pH. The highest soil available N, K and Mg was recorded in treatment T5 which also showed highest plant content of Mg, Zn and Cu. The acid sulphate soils of Kuttanad region are having constraints of extreme acidic soil pH and pronounced toxicity of Fe and Al. This can be ameliorated using amendments and can be made more productive. The results of the investigation clearly indicate that application of phosphogypsum along with lime and foliar application of B and Si enhances the grain and straw yield of rice. This treatment also enhanced the available nutrient status of soil and plant nutrient content. It was very effective in alleviating toxicity of Fe and Al.